Astaxanthin Protects Against H2O2- and Doxorubicin-Induced Cardiotoxicity in H9c2 Rat Myocardial Cells - Roman Krestinin; Margarita Kobyakova; Yulia Baburina; Linda Sotnikova; Olga Krestinina (Life)
Astaxanthin (AST) is a carotenoid that has positive effects on various organs and tissues. It also exhibits a cardioprotective action. In this study, the influence of AST on the survival of H9c2 cardiomyocytes under hydrogen peroxide (H2O2)- and doxorubicin (DOX)-induced cardiotoxicity was investigated. Under these conditions, the content of cytosolic Ca2+ was measured, and changes in the area of the mitochondrial mass, as well as in the content of the voltage-dependent anion channel 1 (VDAC1), the autophagy marker LC3A/B, and the pro-apoptotic transcription factor homologous protein (CHOP), were determined. It was found that AST removed the cytotoxic effect of H2O2 and DOX, while cell survival increased, and the mitochondrial mass did not differ from the control. At the same time, a decrease in the content of cytosolic Ca2+ and the restoration of the VDAC1 level to values close to the control were observed. The restoration of the CHOP level suggests a reduction in endoplasmic reticulum (ER) stress in cells. The results allow us to consider AST as a potential agent in the prevention and/or treatment of cardiac diseases associated with oxidative stress.